Exciton Relaxation and Polaron Formation in LH2 at Low Temperature - Polívka, Tomáš; Pullerits, Tõnu; Herek, Jennifer L.; Sundström, Villy (Journal of Physical Chemistry B, 2000)
Excited state dynamics of antenna complexes in an LH2-only mutant of the purple bacterium Rb. sphaeroides have been investigated by means of two-color femtosecond spectroscopy combined with computer simulations. Measurements of transient absorption spectra revealed a new spectral band in the stimulated emission region around 880 nm at 6 K. To simulate this new dynamic feature that appears within the first 2 ps after light absorption, we have used a simplified polaron model via a decoupled red pigment within the B850 ring. Comparison of simulations and experiment suggests the following kinetic scheme:  (1) initial ultrafast (∼100 fs) dynamics correspond to exciton relaxation to the lowest exciton state; (2) mixing of the lowest exciton state with charge-transfer states results in a relaxation to these states in about 600 fs; (3) picosecond dielectric relaxation in the charge-transfer states corresponding to polaron formation follows.